The Ontology of the Amphioxus Anatomy and Life Cycle (AMPHX) - Bertrand, Stephanie; Carvalho, João E.; Dauga, Delphine; Matentzoglu, Nicolas; Daric, Vladimir; Yu, Jr-Kai; Schubert, Michael; Escrivá, Hector (Frontiers in Cell and Developmental Biology, 2021)
An ontology is a computable representation of the different parts of an organism and its different developmental stages as well as the relationships between them. The ontology of model organisms is therefore a fundamental tool for a multitude of bioinformatics and comparative analyses. The cephalochordate amphioxus is a marine animal representing the earliest divergent evolutionary lineage of chordates. Furthermore, its morphology, its anatomy and its genome can be considered as prototypes of the chordate phylum. For these reasons, amphioxus is a very important animal model for evolutionary developmental biology studies aimed at understanding the origin and diversification of vertebrates. Here, we have constructed an amphioxus ontology (AMPHX) which combines anatomical and developmental terms and includes the relationships among these terms. AMPHX will be used to annotate amphioxus gene expression patterns as well as phenotypes. We encourage the scientific community to adopt this amphioxus ontology and send recommendations for future updates and improvements.